The Burden of HIV Infection among Pregnant Women Attending Antenatal Care in Jimma University Specialized Hospital in Ethiopia: A Retrospective Observational Study - Kebede, Taye; Dayu, Michael; Girma, Abiot (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. The HIV (human immunodeficiency virus) epidemic enters its fifth decade amid a global pandemic. Nearly 61% of the people newly infected with HIV live in sub-Saharan Africa (SSA). The virus is transmitted from mother to child during pregnancy, labour, delivery, and breastfeeding, warranting routine counselling at antenatal care (ANC). Hence, this study aimed to determine the prevalence and trend of HIV infection among pregnant women on ANC follow-up at Jimma University Specialized Hospital (JUSH) in Ethiopia from November 2018 to 2021. Methods. A retrospective cross-sectional study was conducted from June 25, 2021, to November 30, 2021. A total of 634 mothers were sampled by systematic random sampling, and the data were analyzed by descriptive statistics package of SPSS software. A chi-square test was employed to assess an association between variables. Analyses outputs were summarized and presented in tables and figures. Results. Among the sampled women (634), 96.1% received counselling services on the prevention of maternal-to-child transmission of HIV/AIDS. Around 83.1% of the mothers refused to consult their partners and were unable to persuade their surrogate or afraid to discuss HIV serostatus tests. The overall prevalence of HIV infection among pregnant mothers was 7.1% and no significant decrease in the trends of HIV prevalence over the three years study period (p value >0.05). The seroprevalence is high in urban residents (4.4%) and age group of 25–29 years (38.9%) (p value <0.05). Residence, level of education attained, and marital status of women were significantly associated (p value <0.05) with seropositivity. Conclusion. HIV burden among ANC attendees in JUSH is high as compared to the national figure and its trend over three years is steady. Accordingly, mandatory early screening tests and community-based education are mandatory for all women and adolescent girls in the reproductive age group.